Pengaruh Permodalan, Risiko Kredit, dan Efisiensi Operasional terhadap Kinerja Keuangan Bank Umum Konvensional yang Terdaftar di BEI Periode 2023-2025 - Risalatun Nisa’ Febryanti; Puji Astuti; Badrus Zaman (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
This study is motivated by the importance of financial performance in maintaining stability, sustainability, and public trust in the banking industry. Financial performance is influenced by several factors, including capital adequacy, credit risk, and operational efficiency. However, previous studies regarding the effect of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), and Operating Expenses to Operating Income (BOPO) on Return on Assets (ROA) have produced inconsistent findings. Therefore, this study aims to analyze the effect of CAR, NPL, and BOPO on ROA in Conventional Commercial Banks listed on the Indonesia Stock Exchange during the 2023–2025 period, both partially and simultaneously. This research uses a quantitative approach with a causal design. Secondary data were obtained from annual financial reports, with samples selected through purposive sampling, resulting in 26 banks and 78 observations. Data were analyzed using multiple linear regression. The findings show that CAR and NPL partially have no significant effect on ROA, while BOPO has a negative and significant effect. Simultaneously, CAR, NPL, and BOPO significantly affect ROA, with an Adjusted R² value of 0.820.